PEMBERIAN REBUSAN DAUN SAMBILOTO (ANDROGRAPHIS PANICULATA) PADA PENDERITA DIABETES MELLITUS - Awaluddin Awaluddin; Ulul Fadhli Rahim (Jurnal Keperawatan Abdurrab, 2026)
Indonesia ranks fifth in the world for the number of diabetes sufferers. Diabetes can be managed pharmacologically and non-pharmacologically. One non-pharmacological therapy is the consumption of boiled sambiloto (Andrographis paniculata) leaves. This study aims to determine the effect of boiled sambiloto leaves on random blood sugar levels in diabetes mellitus patients. The research design used was a Quasi-Experimental with a one-group pre-test post-test design. This study was conducted in Kepenuhan Barat Mulya Village in January 2025. The sampling technique used total sampling, with 24 respondents. Data collection tools were observation sheets and a glucometer. The data were analyzed using the Wilcoxon Signed Rank Test. The results of this study showed that before consuming the bitter leaf decoction, the average blood sugar level of respondents was 304 mg/dL, with a range of 201–573 mg/dL. After administering the bitter leaf decoction, blood sugar levels decreased to an average of 194 mg/dL, with a range of 132- 298 mg/dL. The results of the Wilcoxon Signed Ranks Test indicate a significant effect of bitter leaf decoction on reducing blood sugar levels in people with diabetes mellitus. Thus, the use of this herbal plant can be a natural option in helping control blood sugar levels, especially for people with diabetes who are looking for a safer and more effective alternative treatment.